2012
DOI: 10.1155/2012/582748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxidative Stress in Fetal Programming

Abstract: Intrauterine stress induces increased risk of adult disease through fetal programming mechanisms. Oxidative stress can be generated by several conditions, such as, prenatal hypoxia, maternal under- and overnutrition, and excessive glucocorticoid exposure. The role of oxidant molecules as signaling factors in fetal programming via epigenetic mechanisms is discussed. By linking oxidative stress with dysregulation of specific target genes, we may be able to develop therapeutic strategies that protect against orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
205
2
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(218 citation statements)
references
References 113 publications
7
205
2
4
Order By: Relevance
“…Numerous studies have demonstrated that ROS scavengers such as n-acetylcysteine and tempol prevent epigenetic DNA methylation changes induced by oxidative stress (149)(150)(151). Similarly, oxidative stress mediated by intrauterine hypoxia was shown to be protected by administering DNMT inhibitors (137) or methyl donors such as genistein (152,153). Taken together, these studies demonstrate that exogenous application of antioxidant supplements protects the biological system by preventing aberrant epigenetic transformations.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Numerous studies have demonstrated that ROS scavengers such as n-acetylcysteine and tempol prevent epigenetic DNA methylation changes induced by oxidative stress (149)(150)(151). Similarly, oxidative stress mediated by intrauterine hypoxia was shown to be protected by administering DNMT inhibitors (137) or methyl donors such as genistein (152,153). Taken together, these studies demonstrate that exogenous application of antioxidant supplements protects the biological system by preventing aberrant epigenetic transformations.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous epidemiological studies support the role of oxidative stress as a mechanistic basis for fetal programing (137)(138)(139). For example, low birth weight is often associated with elevated oxidative stress during intrauterine development, resulting in cardiovascular disease and type 2 diabetes in adulthood (140).…”
Section: Fetal and Developmental Radiation Concernsmentioning
confidence: 99%
“…Nonetheless, many authors (reviews in Luo et al 2006;Nuyt and Alexander 2009;Tarry-Adkins et al 2009;Dennery 2010;Hernandez-García et al 2010;Warner and Ozanne 2010;Thompson and Al-Hasan 2012) have noted that most of the cited mechanisms involve oxidative stress, which is the imbalance between the production of reactive species by cell metabolism or immune responses and the state and availability of antioxidant defenses (Halliwell and Gutteridge 2007). Oxidative stress was initially proposed as one of the main proximate causes of aging (e.g., Kirkwood and Austad 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress has been proposed as a potential mediator of nutrition-induced epigenetic changes through various experimental models (40). Maternal malnutrition, obesity or obesogenic maternal diet during gestation, but not during postweaning period (41), was associated with increased oxidative stress markers and impaired antioxidant capacity in the offspring, making them vulnerable to diabetogenic effects (42,43).…”
Section: Nutrition Triggers Oxidative Stress Early In Lifementioning
confidence: 99%